Effect of Tax Avoidance and Tax Evasion on Personal Income Tax Administration in Nigeria - Adebisi, J. F; Gbegi, Daniel Orsaa (American Journal of Humanities and Social Sciences, 2013)
<!–[if gte mso 9]> <![endif]–> The study examines the effect of tax avoidance and tax evasion on personal income tax administration in Nigeria. Tax evasion and tax avoidance, a problem which seems to have defied solution, had been deviled the tax system right from colonial times. While some had blamed the situation on tax authorities for not living up to expectation with regards to tax administration, others attribute it to the unpatriotic attitude of tax payers. It was in this light of contending position that the researcher carryout a survey in Nigeria with particular reference to Federal Inland Revenue Service Abuja. The sample size was derived statistically using Yaro Yamani formula. The sample size consists of three hundred and five (305) employees of Federal Inland Revenue Service Abuja. The study utilizes primary and secondary data. Tables and percentages were used for the analysis. The Analysis of Variance (ANOVA) was used to test the hypotheses. The research findings disclose that enlightenment and adequate utilization of tax revenue on public goods will discourage tax avoidance and tax evasion, high tax rates encourage tax avoidance and tax evasion, personal income tax generation has not being impressive and personal income tax rates are too high. The researcher therefore concluded that there is a direct and positive relationship between tax avoidance, tax evasion, tax rates and personal income tax administration in Nigeria. Hence recommended that tax officials should be constantly trained and retrained on the job, a deliberate and more aggressive public enlightenment campaign should be embarked upon by government and the reduction in tax rates for the poor. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; text-align:justify; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –>